ACCEPTABILITY PURPLE SWEET POTATO BUTTER CAKE AND CARBOHYDRATE ANALYSIS FOR DIABETICS SNACK - Novilia, Cindy; Fitri, Fitri; Alza, Yessi (JURNAL IBU DAN ANAK, 2018)
Purple sweet potato is a functional food, containing high anthocyanins, fiber, amylose and low glycemic index. Sweet potato is one of carbohydrates source that potentially as local resources for an effort of staple food diversification. Cake is popular bakery products that have sweet taste and soft texture. Butter cake gives distinctive aroma of butter and savory favored. In Indonesia, patients with diabetes mellitus have increasing from 1.1% (2007) to 1.5% (2013). Snack for diabetics must have appropriate nutritional value and can control blood glucose to prevent the risk of complications in patients with diabetes mellitus. Diabetics need snacks that have appropriate nutritional value that does not cause hypo/hyperglycemia. This study is based on experimental research design using a randomized block design (RAK) with 3 formula substitution of wheat flour and purple sweet potato and 1 control, organoleptic (sensory) test and analysis of carbohydrates. Organoleptic (sensory) data were analyzed using One Way ANOVA, and carbohydrate test data were analyzed using Luff Schrool methods. Our result in the research on the acceptability purple sweet potato butter cake showed significant real difference of the sensory score included flavour, aroma, colour and texture by used 75% concentration of purple sweet potato and also increases the sensory scores of the product, resistant starch content and acceptability of cake. The carbohydrates analysis of purple sweet potato butter cake showed that the starch in butter cake with 75% concentrate of purple sweet potato is 27.77%.